Photosensitive resin composition containing polyamic acid microspheres, photosensitive resin sheet and application thereof
By using polyamic acid microspheres in the photosensitive resin composition, combining alkali-soluble resins and other additives, the shortcomings of the existing resin composition in terms of modulus, resolution and mechanical properties are solved, and a high-performance resin combination is achieved It is suitable for semiconductor components and electronic components.
Patent Information
- Application Number
- CN202410706953.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-03
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-06-03
Smart Images

Figure QLYQS_1 
Figure QLYQS_2 
Figure QLYQS_3
Abstract
Description
Technical Field
[0001] The present invention relates to a photosensitive resin composition, in particular to a photosensitive resin composition containing polyamic acid microspheres, a preparation method of the photosensitive resin composition, and a photosensitive resin sheet, a photosensitive resin film, an electronic component or a semiconductor device made from the photosensitive resin composition. Background Art
[0002] In recent years, various packaging forms have been proposed to achieve high performance and low cost for semiconductor devices and electronic components. In order to obtain highly integrated and miniaturized hollow structure electronic devices, the method of using photosensitive dry films that are easier to miniaturize and lower in height to build hollow structures has become the mainstream. Usually, when packaging RF front-end modules, etc., plastic sealing materials with higher potting temperatures are required. Therefore, the photosensitive layer needs to have a higher glass transition temperature to ensure that the cover will not soften, collapse, or crack during the chip plastic sealing process.
[0003] In order to meet the above requirements, a resin composition that can be patterned by photolithography is required. In addition to meeting the characteristics of low stress, high adhesion, high insulation reliability, and good heat resistance, the resin composition used needs to achieve a high resolution to expose the electrode part to ensure inter-chip conduction, and the photosensitive layer needs to have a high modulus to support its cover structure.
[0004] In the prior art, the modulus of the cured resin film is usually increased by adding a variety of inorganic fillers to the resin. Patent 112251023A discloses a high-strength and high-modulus polyimide film prepared from polyamic acid, epoxy resin, aluminum oxide, silane treatment agent, and erucic acid amide. Patent CN114730127A discloses a glass filler containing free silicon oxide, aluminum oxide, and boron oxide and containing rare earth oxides. A photosensitive resin composition is prepared by reacting with a polymer, a photopolymerizable compound, and a photopolymerization initiator. The photosensitive resin composition can form an insulating film with excellent pattern processing and pressure resistance and high reliability, and is suitable for substrates requiring high elastic modulus and high resolution, and for electronic components with hollow structures requiring pressure resistance. CN113646882A uses alkali-soluble polyimide, a compound containing an unsaturated bond, a thermally crosslinkable compound, a photopolymerization initiator, an inorganic filler, and a silane coupling agent to prepare a high modulus, photosensitive resin composition that can form a photolithographic pattern. The addition of inorganic fillers will lead to problems such as reduced mechanical properties of the membrane, poor resolution and adhesion. Summary of the invention
[0005] In view of the above situation, the purpose of the present invention is to provide a photosensitive resin composition, which contains polyamic acid microspheres and has excellent resolution. The cured film formed by the photosensitive resin composition has high modulus, excellent mechanical properties, good adhesion to the substrate, and can effectively prevent oxidation and discoloration of the copper substrate surface.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions:
[0007] A photosensitive resin composition comprises polyamic acid microspheres A, alkali-soluble resin B, crosslinking agent C, photoinitiator D and solvent E. The polyamic acid microspheres A are obtained by emulsifying and crosslinking polyamic acid, and the polyamic acid comprises polyamic acid obtained by polymerization reaction of diamine X and aromatic dianhydride Y.
[0008] Further, the diamine X includes a diamine compound X-1 and a diamine compound X-2, wherein the diamine compound X-1 is at least one of the photopolymerizable diamine compounds shown in Formula I, and the diamine compound X-2 is at least one of the non-photopolymerizable diamine compounds;
[0009]
[0010]
[0011] In formula I, Ar is selected from one of phenyl, naphthyl, biphenyl and diphenyl ether;
[0012] R1 is selected from one of hydrogen atom, methyl, ethyl, hydroxyl, and methoxyethoxy;
[0013] R2 represents the structure shown in the following formula II, wherein * is an insertion site, and m is 1 or 2;
[0014]
[0015] In formula II, R3 is selected from one of methylene, ethylene, propylene, and phenylene;
[0016] R4 and R5 are independently selected from a hydrogen atom, a methyl group, an ethyl group, a propyl group, and a phenyl group.
[0017] Further, from the perspective of improving the photopolymerizability of the structure represented by formula I, the adhesion to the substrate, and the ease of preparation, the photopolymerizable diamine compound represented by formula I is preferably at least one of the structures represented by the following (b-1) to (b-10):
[0018]
[0019]
[0020] The photopolymerizable diamine structure contains a double bond and undergoes a photopolymerization reaction under light conditions. The resin containing the diamine structure can undergo a cross-linking reaction after emulsification and exposure to light to form polyamic acid microspheres A with a high cross-linking density. The polyamic acid microspheres A have a high glass transition temperature. At the same time, the imidazole ring of the benzimidazole structure can coordinate with the copper atom to form a coordination bond, which can effectively improve the adhesion between the polyimide film and the substrate, and effectively prevent oxidation and discoloration of the copper substrate surface.
[0021] Further, the diamine compound X-2 is selected from 2,2'-bis(3-amino-4-hydroxyphenyl)hexafluoropropane, 2,2'-bis(3-amino-4-hydroxyphenyl)propane, 3,3'-diamino-4,4'-dihydroxybiphenyl, 3,3'-dihydroxy-4,4'-diaminobiphenyl, 3,3'-diamino-4,4'-dihydroxydiphenylmethane, 3,3'-diamino-4,4'-dihydroxydiphenyl sulfide, 3,3'-diamino-4,4'-dihydroxydiphenyl sulfone, p-phenylenediamine, m-phenylenediamine, 2,5-diaminotoluene, 2,6-diaminotoluene, 4,4'-diaminodiphenyl ether, 3,4'-diamino At least one of diphenyl ether, 3,3'-diaminodiphenyl ether, 2,4'-diaminodiphenyl ether, 4,4'-diaminodiphenylmethane, 3,3'-dimethyl-4,4'-diaminodiphenylmethane, 3,3',5,5'-tetramethyl-4,4'-diaminodiphenylmethane, 3,3',5,5'-tetraethyl-4,4'-diaminodiphenylmethane, 4,4'-bis(4-aminophenyl)propane, 4,4'-bis(4-aminophenoxy)diphenyl sulfone, 2,2'-trifluoromethyl-4,4'-diaminodiphenyl ether, 4,4'-bis(4-amino-2-trifluoromethylphenoxy)biphenyl, and 4,4'-diaminodiphenyl sulfone.
[0022] Furthermore, the content of the photopolymerizable diamine compound X-1 represented by Formula I is 50% to 100%, for example, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95%, 100%, based on the total molar amount of diamine X. When the content is 100%, it means that all diamine X is diamine compound X-1.
[0023] Furthermore, the aromatic dianhydride Y for synthesizing the polyamic acid microspheres A is selected from at least one of pyromellitic dianhydride, 4,4'-oxydiphthalic anhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, 2,3',4,4'-biphenyltetracarboxylic dianhydride, and 2,2',3,3'-benzophenonetetracarboxylic dianhydride.
[0024] Furthermore, the photopolymerizable diamine compound of the above formula I of the present invention is prepared by itself, and the preparation method thereof comprises the following steps:
[0025] Step 1: The compound represented by the structure of formula (1) and the compound represented by the structure of formula (2) react in the presence of catalyst 1 to generate a compound represented by the structure of formula (3);
[0026]
[0027] Wherein, X is F, Cl, Br or I, preferably Cl; R6 is methyl, ethyl or propyl; R3, R4, R5 have the same definitions as above;
[0028] Step 2: The compound of the structure shown in formula (3) and the dinitro compound of the structure shown in formula (4) react in the presence of catalyst 2 to generate a compound of the structure shown in formula (5);
[0029]
[0030] Wherein, m, Ar, R1, R2, R3, R4, and R5 are defined the same as above;
[0031] Step 3: reducing the nitro group in the compound of the structure shown in formula (5) to obtain a photopolymerizable diamine of the structure shown in formula I;
[0032]
[0033] In the above preparation method, the raw materials used are all common raw materials in the field, which can be purchased from the market or prepared according to the methods disclosed in the prior art. The synthesis method is simple and has a high yield.
[0034] Furthermore, in step 1, catalyst 1 is added dropwise into a mixture of a compound of formula (2) and a solvent, and then a compound of formula (1) is added to react, and a compound of formula (3) is obtained after post-treatment.
[0035] Furthermore, in step 1, the catalyst 1 is boron trifluoride etherate. The catalyst 1 is dripped at a rate of one drop per 0.1 to 5 seconds.
[0036] Further, in step 1, the solvent is a low boiling point organic solvent having a boiling point of less than or equal to 70°C, such as dichloromethane, chloroform or tetrahydrofuran. The solvent mainly acts as a reaction medium, and its amount can be adjusted according to actual needs. In a specific embodiment of the present invention, the mass ratio of the compound of the structure shown in formula (2) to the low boiling point solvent is 1:10 to 100, such as 1:10, 1:30, 1:50, 1:80, 1:100.
[0037] Furthermore, in step 1, the molar ratio of the compound having the structure represented by formula (2) to the compound having the structure represented by formula (1) is 1-2:1.
[0038] Furthermore, in step 1, the molar ratio of catalyst 1 to the compound of the structure represented by formula (1) is 0.9-1.1:1.
[0039] Further, in step 1, the reaction temperature is -10 to 30° C., for example, -10° C., -5° C., 0° C., 5° C., 10° C., 15° C., 20° C., 25° C., 30° C., preferably -5 to 10° C. At this reaction temperature, the general reaction time is 0.5 to 8 h, for example, 0.5 h, 1 h, 2 h, 3 h, 4 h, 5 h, 6 h, 7 h, 8 h, 9 h, preferably 2 to 6 h.
[0040] Furthermore, in step 1, after the reaction, the reaction is quenched with a saturated NaHCO3 aqueous solution, and then post-processed by extraction, drying, and column chromatography to obtain a compound with a structure shown in formula (3).
[0041] Furthermore, in step 2, in the presence of catalyst 2 and a solvent, the compound represented by formula (3) and the dinitro compound represented by formula (4) are reacted, and the compound represented by formula (5) is obtained after post-treatment.
[0042] Furthermore, in step 2, the reaction is carried out under an inert atmosphere; the inert atmosphere is selected from at least one of inert gases such as nitrogen and argon.
[0043] Furthermore, in step 2, the catalyst 2 is selected from at least one of potassium carbonate and sodium carbonate.
[0044] Further, in step 2, the solvent is selected from at least one of 1,4-dioxane, N-methylpyrrolidone, N-ethylpyrrolidone, and dimethylformamide. The solvent mainly acts as a reaction medium, and its amount can be adjusted according to actual needs. In a specific embodiment of the present invention, the mass ratio of the total mass of the compound represented by formula (3) and the dinitro compound represented by formula (4) to the solvent is 1:1 to 5, for example, 1:1, 1:2, 1:3, 1:4, 1:5.
[0045] Further, the reaction temperature of step 2 is 50-120° C., for example, 50° C., 60° C., 70° C., 80° C., 90° C., 100° C., 110° C., 120° C., preferably 60-100° C. At this reaction temperature, the reaction time is generally 5-30 h, for example, 5 h, 10 h, 15 h, 20 h, 25 h, 30 h, preferably 10-20 h.
[0046] Further, in step 2, the molar ratio of the hydroxyl groups participating in the reaction in the compound represented by formula (3) to the compound represented by formula (4) is 1:0.9-1.1. Optionally, the molar ratio of the hydroxyl groups in the compound represented by formula (3) to the compound represented by formula (4) is independently selected from any value among 1:0.90, 1:0.95, 1:1.0, 1:1.05, 1:1.10, or any range between the two.
[0047] Further, in step 2, the molar ratio of catalyst 2 to the compound represented by formula (3) is 1 to 3: 1. Optionally, the molar ratio of catalyst 2 to the compound represented by formula (3) is independently selected from any value of 1.0: 1, 1.5: 1, 2.0: 1, 2.5: 1, 3.0: 1 or any range between the two.
[0048] Furthermore, in step 2, the post-treatment includes filtering the reaction solution, washing and drying the obtained precipitate. Preferably, the precipitate is washed with water.
[0049] Furthermore, in step three, the reaction is carried out in the presence of a catalyst and a solvent, wherein the catalyst is catalyst 3 and catalyst 4. Catalyst 3 and catalyst 4 are added to a solution containing a compound having a structure represented by formula (5) to carry out a reaction, so that the nitro group in the compound having a structure represented by formula (5) is reduced to an amino group, and a diamine having a structure represented by formula I is obtained after post-treatment.
[0050] Furthermore, in step three, the catalyst 3 is zinc powder, and the catalyst 4 is glacial acetic acid.
[0051] Further, in step 3, the molar ratio of catalyst 3 to the compound of the structure represented by formula (5) is 10-30:1, for example, 10:1, 12:1, 15:1, 18:1, 20:1, 22:1, 25:1, 30:1. The molar ratio of catalyst 4 to the compound of the structure represented by formula (5) is 10-30:1, for example, 10:1, 12:1, 15:1, 18:1, 20:1, 22:1, 25:1, 30:1.
[0052] Further, in step 3, the solvent is at least one of the alcohol solvents having 1 to 5 carbon atoms, such as anhydrous methanol, anhydrous ethanol, etc. The solvent mainly acts as a reaction medium, and its amount can be adjusted according to actual needs. In a specific embodiment of the present invention, the mass ratio of the compound of the structure shown in formula (5) to the alcohol solvent is 1:5 to 30, such as any value in 1:5, 1:6, 1:7, 1:8, 1:9, 1:10, 1:15, 1:20:, 1:25, 1:30 or any range value between the two.
[0053] Furthermore, in step 3, the reaction temperature is 15-35° C., for example, 15° C., 20° C., 25° C., 30° C., 35° C. At this reaction temperature, the reaction time is generally 0.5-3 h, for example, 0.5 h, 1 h, 2 h, 3 h.
[0054] Furthermore, in step 3, the post-treatment includes the steps of filtering the reaction solution, removing the solvent by vacuum distillation, extraction, washing the organic phase, removing the extractant by vacuum distillation, and drying. The filtering is preferably performed using diatomaceous earth filtration, the extraction is performed using ethyl acetate, dichloromethane, or chloroform, and the washing is preferably performed using a saturated NaCl solution.
[0055] As a preferred technical solution, the method for preparing the photopolymerizable diamine comprises the following steps:
[0056] Step 1: Dissolve the compound of formula (2) in dry dichloromethane at 0°C, add catalyst 1 dropwise, then add the compound of formula (1), stir and react at room temperature for 2-2.5 hours, and detect by TLC plate. When the compound of formula (1) is completely reacted, the reaction is quenched, extracted, dried, and column chromatographed to obtain a compound of formula (3).
[0057] Step 2: In a nitrogen atmosphere, dimethylformamide, catalyst 2, the compound of formula (3) and the compound of formula (4) are added to a three-necked flask, heated to 80°C and stirred for reaction for 16 hours. Thereafter, the compound of formula (5) is obtained by filtering, washing and drying.
[0058] Step 3: At room temperature, catalyst 3 and catalyst 4 are added to an ethanol solution containing a compound having a structure represented by formula (5), stirred for 1 hour, and then subjected to post-treatment such as filtration, reduced pressure distillation, extraction, washing, and drying to obtain a diamine compound having a structure represented by formula I.
[0059] Furthermore, the polyamic acid microspheres A of the present invention are polyimide spherical structures, and their particle size is 150-250nm, for example, 150nm, 155nm, 160nm, 165nm, 170nm, 175nm, 180nm, 185nm, 190nm, 195nm, 200nm, 205nm, 210nm, 215nm, 220nm, 225nm, 230nm, 235nm, 240nm, 245nm, and 250nm.
[0060] Furthermore, the polyamic acid microspheres A of the present invention can be one, two or more, and at least one polyamic acid microsphere A is obtained by polymerization of a diamine compound X and an aromatic dianhydride Y.
[0061] Furthermore, when the diamine compound X of the present invention reacts with the aromatic dianhydride Y to prepare the polyamic acid microsphere A, the following steps are included: firstly reacting the diamine and the aromatic dianhydride Y to obtain polyamic acid; and then emulsifying and crosslinking the polyamic acid to obtain the polyamic acid microsphere A.
[0062] Further, the preparation of polyamic acid can be carried out by the method of the prior art, and the reaction of diamine X and aromatic dianhydride Y is carried out in an organic solvent to obtain a polyamic acid solution. As long as the organic solvent can dissolve the generated polyamic acid, N, N-dimethylformamide, N, N-dimethylacetamide, N-methylpyrrolidone, N-methylcaprolactam, dimethyl sulfoxide, γ-butyrolactone, etc. can be specifically listed. In addition, when the solubility of polyamic acid is high, methyl ethyl ketone, cyclohexanone, cyclopentanone, 4-hydroxy-4-methyl-2-pentanone, etc. can be used. The above-mentioned organic solvents can be used alone or in combination. Since the moisture in the organic solvent inhibits the polymerization reaction, the organic solvent can be used after dehydration and drying.
[0063] Examples of the method for reacting the diamine X and the aromatic dianhydride Y in an organic solvent include a method of directly adding the aromatic dianhydride Y or adding the aromatic dianhydride Y after dispersing or dissolving the aromatic dianhydride Y in an organic solvent by stirring the diamine X to obtain a solution; a method of adding the diamine X to a solution obtained by dispersing or dissolving the aromatic dianhydride Y in an organic solvent; a method of adding the aromatic dianhydride Y and the diamine X to the organic solvent alternately or simultaneously, and any of the above methods may be used.
[0064] The temperature during synthesis of polyamic acid can be selected from any temperature of -20 to 150°C, for example, -20°C, -15°C, -10°C, -5°C, 0°C, 5°C, 10°C, 15°C, 20°C, 25°C, 30°C, 35°C, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C, 100°C, 105°C, 110°C, 115°C, 120°C, 125°C, 130°C, 135°C, 140°C, 145°C, 150°C, preferably 0 to 80°C. The reaction time is preferably 1 to 72 hours, for example, 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, 15h, 20h, 25h, 30h, 35h, 40h, 45h, 48h, 50h, 60h, 70h, 72h, more preferably 2 to 48 hours. The mass concentration of the reactants is preferably 1 to 50%, for example, 1%, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, more preferably 5 to 20%. When the reaction concentration is too low, it is difficult to obtain a polymer with a high molecular weight. When the reaction concentration is too high, the viscosity of the reaction solution is too large, making it difficult to stir evenly. During the reaction, the ratio of the molar amount of aromatic dianhydride Y to the molar amount of diamine X is 1:0.8 to 1.2. Generally, the closer the molar ratio is to 1:1, the greater the molecular weight of the generated polyamic acid.
[0065] After the polyamic acid solution is synthesized, the polyamic acid solution is diluted with an organic solvent, an organic amine and a photoinitiator are added and stirred to mix evenly, and then a poor solvent is added and stirred to emulsify to obtain a polyamic acid emulsion, and the polyamic acid emulsion is irradiated under ultraviolet light for cross-linking. After cross-linking, the product is precipitated in water, filtered, and dried to obtain polyamic acid microspheres A.
[0066] Furthermore, the organic solvent only needs to be able to dissolve the generated polyamic acid, and specific examples include N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, N-methylcaprolactam, dimethyl sulfoxide, γ-butyrolactone, etc., which can be used alone or in combination.
[0067] Furthermore, the organic amine is triethylamine, etc. The photoinitiator is the same as the photoinitiator D. The poor solvent is methanol, ethanol, water, acetone, etc.
[0068] Further, the polyamic acid solution is diluted with an organic solvent to a polyamic acid mass concentration of 1 to 10%, such as 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%. The molar amount of the organic amine is 50 to 200% of the aromatic dianhydride Y, such as 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95%, 100%, 110%, 120%, 130%, 140%, 150%, 160%, 170%, 180%, 190%, 200%. The mass of the photoinitiator is 0.1-20% of the mass of the polyamic acid, for example, 0.1%, 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%. The mass of the poor solvent is 50-200% of the mass of the organic solvent in the diluted polyamic acid solution, for example, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95%, 100%, 110%, 120%, 130%, 140%, 150%, 160%, 170%, 180%, 190%, 200%.
[0069] Furthermore, the emulsification reaction temperature is 10-50° C., for example, 10° C., 15° C., 20° C., 25° C., 30° C., 35° C., 40° C., 45° C., 50° C. The reaction time is 0.5-5 h, for example, 0.5 h, 1 h, 2 h, 3 h, 4 h, 5 h.
[0070] Furthermore, the wavelength of the ultraviolet light is 365-405 nm, and the ultraviolet irradiation time is 0.5-8 h, for example 0.5 h, 1 h, 1.5 h, 2 h, 2.5 h, 3 h, 3.5 h, 4 h, 4.5 h, 5 h, 5.5 h, 6 h, 6.5 h, 7 h, 7.5 h, and 8 h.
[0071] Furthermore, after ultraviolet irradiation, water is added for precipitation, and the mass of water used for precipitation is 200-1000% of the mass of the solution obtained after ultraviolet irradiation, for example, 200%, 250%, 300%, 350%, 400%, 450%, 500%, 550%, 600%, 650%, 700%, 750%, 800%, 850%, 900%, 950%, 1000%.
[0072] Further, the drying can be carried out in a drying box, and the drying temperature is 50-200° C., for example, 50° C., 55° C., 60° C., 65° C., 70° C., 75° C., 80° C., 85° C., 90° C., 95° C., 100° C., 110° C., 120° C., 130° C., 140° C., 150° C., 160° C., 170° C., 180° C., 190° C., 200° C. The drying time is 2-72 h, for example, 2 h, 3 h, 4 h, 5 h, 6 h, 7 h, 8 h, 9 h, 10 h, 15 h, 20 h, 25 h, 30 h, 35 h, 40 h, 45 h, 48 h, 50 h, 60 h, 70 h, 72 h.
[0073] The alkali-soluble resin B may be at least one of polyamic acid, polyamic acid ester and polyimide. Alkali-soluble means that the amount of the resin dissolved in 100g of 2.38wt% tetramethylammonium hydroxide aqueous solution at 25°C is 0.1g or more.
[0074] Furthermore, the alkali-soluble resin B is at least one of alkali-soluble polyimide, alkali-soluble polyamic acid, and alkali-soluble polyamic acid ester, which are obtained by reacting a tetracarboxylic dianhydride compound with a diamine compound.
[0075] Preferably, the tetracarboxylic dianhydride compound is selected from at least one of pyromellitic dianhydride, 3,4,3',4'-biphenyltetracarboxylic dianhydride, 4,4'-oxydiphthalic anhydride, 3,4,3',4'-benzophenonetetracarboxylic dianhydride, 3,3',4,4'-diphenylsulfonetetracarboxylic dianhydride, 2,3,6,7-naphthalenetetracarboxylic dianhydride, 4,4'-(hexafluoroisopropylidene)diphthalic anhydride and 1,2,3,4-cyclobutanetetracarboxylic dianhydride.
[0076] Preferably, the diamine compound is selected from 2,2'-bis(3-amino-4-hydroxyphenyl)hexafluoropropane, 2,2'-bis(3-amino-4-hydroxyphenyl)propane, 3,3'-diamino-4,4'-dihydroxybiphenyl, 3,3'-dihydroxy-4,4'-diaminobiphenyl, 3,3'-diamino-4,4'-dihydroxydiphenylmethane, 3,3'-diamino-4,4'-dihydroxydiphenyl sulfide, 3,3'-diamino-4,4'-dihydroxydiphenyl sulfone, p-phenylenediamine, m-phenylenediamine, 2,5-diaminotoluene, 2,6-diaminotoluene, 4,4'-diaminodiphenyl ether, 3,4'-diaminodiphenyl ether, 3,3'-diamino At least one of diphenyl ether, 2,4'-diaminodiphenyl ether, 4,4'-diaminodiphenylmethane, 3,3'-dimethyl-4,4'-diaminodiphenylmethane, 3,3',5,5'-tetramethyl-4,4'-diaminodiphenylmethane, 3,3',5,5'-tetraethyl-4,4'-diaminodiphenylmethane, 4,4'-bis(4-aminophenyl)propane, 4,4'-bis(4-aminophenoxy)diphenyl sulfone, 2,2'-trifluoromethyl-4,4'-diaminodiphenyl ether, 4,4'-bis(4-amino-2-trifluoromethylphenoxy)biphenyl, 4,4'-diaminodiphenyl sulfone and 1,3-bis(3-aminopropyl)tetramethyldisiloxane.
[0077] Furthermore, the alkali-soluble resin can be prepared by the following method:
[0078] (1) Preparation method of polyamic acid
[0079] The polyamic acid can be obtained by reacting a diamine compound with a tetracarboxylic dianhydride in an organic solvent. The specific preparation method can refer to the preparation method of the polyamic acid in the polyamic acid microsphere A above.
[0080] (2) Preparation method of polyamic acid ester
[0081] (2.1) Preparation from polyamic acid
[0082] The polyamic acid ester can be prepared by esterification reaction of the polyamic acid. Specifically, the polyamic acid and the esterification agent are reacted in an organic solvent at -20 to 150° C., preferably 0 to 50° C., for 0.5 to 24 hours, preferably 1 to 4 hours.
[0083] As the esterifying agent, an esterifying agent that can be easily removed by purification is preferred, and examples thereof include N,N-dimethylformamide dimethyl acetal, N,N-dimethylformamide diethyl acetal, N,N-dimethylformamide dipropyl acetal, N,N-dimethylformamide dineopentyl butyl acetal, N,N-dimethylformamide di-tert-butyl acetal, 1-methyl-3-tolyl triazene, 1-ethyl-3-p-tolyl triazene, 1-propyl-3-p-tolyl triazene, 4-(4,6-dimethoxy-1,3,5-triazine-2-yl)-4-methylmorpholinochloride, and the like. The amount of the esterifying agent added is in a molar ratio of 2 to 6:1 to the polyamic acid repeating unit.
[0084] The organic solvent may be any solvent as long as it can dissolve the generated polyamic acid ester, and specific examples thereof include N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, N-methylcaprolactam, dimethyl sulfoxide, γ-butyrolactone, etc. In addition, when the solubility of polyamic acid ester is high, methyl ethyl ketone, cyclohexanone, cyclopentanone, and 4-hydroxy-4-methyl-2-pentanone can be used.
[0085] The above organic solvents can be used alone or in combination. Since the water in the organic solvent inhibits the polymerization reaction, the organic solvent can be used after dehydration and drying. From the perspective of polymer solubility, the organic solvent used in the above reaction is preferably N,N-dimethylformamide, N-methylpyrrolidone or γ-butyrolactone, and one or a mixture of two or more can be used. From the perspective of the polymer being difficult to precipitate and having a high molecular weight, the reaction concentration is preferably 1 to 30 wt%, more preferably 5 to 20 wt%.
[0086] (2.2) Preparation by reacting a tetracarboxylic acid diester dichloride compound with a diamine compound: Specifically, the tetracarboxylic acid diester dichloride is reacted with a diamine compound in the presence of a base and an organic solvent at -20 to 150°C, preferably 0 to 50°C for 0.5 to 24 hours, preferably 1 to 4 hours. As the base, pyridine, triethylamine, 4-dimethylaminopyridine, etc. can be used. In order to make the reaction proceed gently, pyridine is preferably used. From the viewpoint of easy removal and easy to obtain a high molecular weight, the amount of base added is equivalent to 2 to 4 times the molar amount of the tetracarboxylic acid diester dichloride, preferably 2 to 3 times the molar amount. From the viewpoint of the solubility of the monomer and the polymer, the solvent used for the above reaction is preferably N-methylpyrrolidone or γ-butyrolactone, and one or a mixture of two or more of the above solvents can be used. From the viewpoint of the polymer being difficult to precipitate and having a high molecular weight, the reaction concentration is preferably 1 to 30 wt%, more preferably 5 to 20 wt%. In order to prevent the hydrolysis of the tetracarboxylic acid diester dichloride, the solvent used for producing the polyamic acid ester is preferably a dehydrated solvent, and the production is performed under nitrogen protection to prevent mixing of the air.
[0087] (2.3) Preparation by polycondensation of tetracarboxylic acid diester and diamine compound: Specifically, it can be prepared by reacting a tetracarboxylic acid diester with a diamine compound in the presence of a condensing agent, a base and an organic solvent at 0 to 150°C, preferably 0 to 100°C for 30 minutes to 24 hours, preferably 3 to 15 hours. As the condensing agent, triphenyl phosphite, dicyclohexylcarbodiimide, 1-ethyl-3-(3-dimethylpropyl)carbodiimide hydrochloride, N,N'-carbonyldiimidazole, dimethyl-1,3,5-triazinylmethylmorpholine, 0-(benzotriazol-1-yl)-N,N,N',N'-tetramethyluronium tetrafluoroborate, 0-(benzotriazol-1-yl)N,N,N',N'-tetramethyluronium hexafluorophosphate, (2,3-dihydro-2-thia-3-benzoxazolyl)diphenyl phosphate, etc. can be used. The amount of the condensing agent added is preferably 2 to 3 times the molar amount of the tetracarboxylic acid diester. As the base, a tertiary amine such as pyridine and triethylamine can be used. From the viewpoint of easy removal and easy to obtain a high molecular weight, the amount of the base added is equivalent to 2 to 4 times the molar amount of the diamine compound component.
[0088] In the above reaction, the reaction can be efficiently carried out by adding a Lewis acid as an additive. The Lewis acid is preferably a halogenated lithium such as lithium chloride or lithium bromide. The amount of the Lewis acid added is 0 to 1.0 times the molar amount of the diamine compound component.
[0089] In order to obtain high molecular weight polyamic acid ester more easily among the above-mentioned 3 methods for producing polyamic acid ester, the production method described in the above (2.1) or (2.2) is preferred.
[0090] The polyamic acid ester solution obtained by the above method is injected into a poor solvent while stirring to precipitate the polymer. After precipitation several times and washing with a poor solvent, it is dried at room temperature or heated to obtain a purified polyamic acid ester powder. The poor solvent is not particularly limited, and water, methanol, ethanol, ethane, butyl cellosolve, acetone, toluene, etc. can be listed.
[0091] (3) Preparation method of polyimide
[0092] The polyimide of the present invention can be prepared by imidization of the aforementioned polyimide precursor (polyamic acid or polyamic acid ester). The imidization rate of the polyimide of the present invention may not be 100%, and can be adjusted according to the use requirements. Regarding the imidization method, a thermal imidization method in which a polyimide precursor is heated without using a catalyst and a catalytic imidization method using a catalyst can be listed.
[0093] When the polyimide precursor is thermally imidized, preferably, the polyimide precursor solution is heated to 100 to 400° C., preferably 120 to 200° C., and thermal imidization is performed while removing water / alcohol generated by the imidization reaction to the outside of the system.
[0094] The catalytic imidization of the polyimide precursor can be carried out by adding a basic catalyst and anhydride to a solution of polyamic acid and stirring at -20 to 250°C, preferably 0 to 180°C. The amount of the basic catalyst is 0.5 to 30 times the molar amount of the amic acid group, preferably 2 to 20 times the molar amount, and the amount of the anhydride is 1 to 50 times the molar amount of the amic acid group, preferably 3 to 30 times the molar amount. As the basic catalyst, pyridine, triethylamine, trimethylamine, tributylamine, trioctylamine, etc. can be listed, among which it is preferred to have a basicity suitable for promoting the reaction, so pyridine is preferred. As the anhydride, acetic anhydride, trimellitic anhydride, pyromellitic anhydride, etc. can be listed, among which, when acetic anhydride is used, it is preferably acetic anhydride considering that it is easy to purify after the reaction is completed. The imidization rate of the catalytic imidization can be controlled by adjusting the amount of catalyst, reaction temperature, and reaction time.
[0095] When recovering the polymer component from the reaction solution of the polyimide, the reaction solution may be put into a poor solvent to precipitate it. Examples of the poor solvent include methanol, acetone, hexane, butyl cellosolve, heptane, methyl ethyl ketone, methyl isobutyl ketone, ethanol, toluene, benzene, water, etc. The polymer obtained by precipitating it by putting into the poor solvent is preferably recovered by filtration and then dried at room temperature under normal pressure or reduced pressure or heated.
[0096] Further, the weight average molecular weight of the alkali-soluble resin B is preferably more than 10,000 and less than 100,000. When the weight average molecular weight is less than 10,000, the mechanical strength is reduced, the bonding strength is weakened, and the weight average molecular weight is preferably more than 12,000. When the weight average molecular weight exceeds 100,000, the developability in the alkaline solution is reduced, and the weight average molecular weight is preferably less than 50,000. In order to adjust the weight average molecular weight of the alkali-soluble resin to an appropriate range, it is preferred to cap at least a portion of the end of the alkali-soluble resin with an aniline derivative or a dicarboxylic anhydride. As the aniline derivative, preferably 2-aminophenol, 3-aminophenol, 4-aminophenol, 2-aminobenzoic acid, 3-aminobenzoic acid, 4-aminobenzenesulfonic acid, 2-aminothiophenol, 3-aminothiophenol, 4-aminothiophenol, 3-aminosalicylic acid, 4-aminosalicylic acid, etc. As the dicarboxylic anhydride, maleic anhydride, phthalic anhydride, nadic anhydride, cyclohexanedicarboxylic anhydride, 5-norbornene-2,3-dicarboxylic anhydride, 1,2-dicarboxynaphthoic anhydride, 3-hydroxyphthalic anhydride and the like are preferred.
[0097] Further, the crosslinking agent C is a photocrosslinking agent, and the photocrosslinking agent reported in the art can be selected, and the following can be listed: diethylene glycol diacrylate, triethylene glycol diacrylate, tetraethylene glycol diacrylate, diethylene glycol dimethacrylate, triethylene glycol dimethacrylate, tetraethylene glycol dimethacrylate, trimethylolpropane diacrylate, trimethylolpropane dimethacrylate, trimethylolpropane trimethacrylate, styrene, α-methylstyrene, 1,2-dihydronaphthalene, 1,3-diisopropenylbenzene, 3-methylstyrene, 4-methylstyrene, p-vinylbenzene, 2-vinylnaphthalene , butyl acrylate, butyl methacrylate, isobutyl acrylate, hexyl acrylate, isooctyl acrylate, isobornyl acrylate, isobornyl methacrylate, cyclohexyl methacrylate, 1,3-butanediol diacrylate, 1,3-butanediol dimethacrylate, neopentyl glycol diacrylate, 1,4-butanediol diacrylate, 1,4-butanediol dimethacrylate, 1,6-hexanediol diacrylate, 1,6-hexanediol dimethacrylate, 1,9-nonanediol dimethacrylate, 1,10-decanediol dimethacrylate, tricyclodecane dimethanol diacrylate, Pentaerythritol triacrylate, pentaerythritol tetraacrylate, pentaerythritol trimethacrylate, pentaerythritol tetramethacrylate, dipentaerythritol hexaacrylate, dipentaerythritol hexamethacrylate, 2-hydroxyethyl acrylate, 2-hydroxyethyl methacrylate, 1,3-diacryloxy-2-hydroxypropane, 1,3-dimethacryloxy-2-hydroxypropane, methylenebisacrylamide, N,N-dimethylacrylamide, N-hydroxymethylacrylamide, 2,2,6,6-tetramethylpiperidinyl methacrylate, N-methyl-2,2,6,6-tetramethylpiperidinyl The crosslinking agents include bisphenol A diacrylate, ethoxylated bisphenol A dimethacrylate, propoxylated bisphenol A diacrylate, propoxylated bisphenol A methacrylate, propoxylated bisphenol A diacrylate, propoxylated bisphenol A dimethacrylate, propoxylated ethoxylated bisphenol A diacrylate, propoxyethoxylated bisphenol A dimethacrylate, N-vinyl caprolactam, polyethylene glycol diacrylate, 2-isocyanatoethyl methacrylate, etc. These crosslinking agents can be one kind or two or more kinds.
[0098] Furthermore, the photoinitiator D can be selected from photoinitiators reported in the art, for example, it can be selected from at least one of benzophenone compounds, benzylidene compounds, coumarin compounds, anthraquinone compounds, benzoin compounds, thioxanthone compounds, thiol compounds, glycine compounds, oxime compounds, α-aminoalkylphenone compounds, 2,2'-bis(o-chlorophenyl)-4,4',5,5'-tetraphenylbiimidazole, and phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide (trade name: 819, manufactured by MERCK). Among them, the benzophenone compound is selected from at least one of benzophenone, 4,4-bis(diethylamino)benzophenone, 3,3,4,4-tetra(tert-butylperoxycarbonyl)benzophenone, etc.; the coumarin compound is selected from benzylidene compounds such as 3,5-bis(diethylaminobenzylidene)-N-methyl-4-piperidone, 3,5-bis(diethylaminobenzylidene)-N-ethyl-4-piperidone, etc.; 7-diethylamino-3-nonyl coumarin, 4,6-dimethyl-3-ethylaminocoumarin, 3,3-carbonylbis(7-diethylaminocoumarin), 7-diethylamino-3-(1- at least one of 2-(methylbenzimidazolyl) coumarin, 3-(2-benzothiazolyl)-7-diethylaminocoumarin, etc.; anthraquinone compounds are selected from anthraquinone compounds such as 2-tert-butylanthraquinone, 2-ethylanthraquinone, 1,2-benzanthraquinone, etc.; benzoin compounds are selected from at least one of benzoin methyl ether, benzoin ethyl ether, benzoin isopropyl ether, etc.; thioxanthone compounds are selected from at least one of 2,4-dimethylthioxanthone, 2,4-diethylthioxanthone, 2,4-diisopropylthioxanthone, 2-isopropylthioxanthone, etc.; mercapto compounds are selected from at least one of ethylene glycol di(3-mercaptopropionate), 2-mercaptobenzothiazole, 2 at least one of 2-mercaptobenzoxazole, 2-mercaptobenzimidazole, etc.; the glycine compound is selected from at least one of N-phenylglycine, N-methyl-N-phenylglycine, N-ethyl-N-(p-chlorophenyl)glycine, N-(4-cyanophenyl)glycine, etc.; the oxime compound is selected from 1-phenyl-1,2-butanedione-2-(o-methoxycarbonyl)oxime, 1-phenyl-1,2-propanedione-2-(o-methoxycarbonyl)oxime, 1-phenyl-1,2-propanedione-2-(o-ethoxycarbonyl)oxime, 1-phenyl-1,2-propanedione-2-(o-benzoyl) oxime, 1-[4-(phenylthio)phenyl]-1,2-octanedione 2-(0-benzoyloxime) (trade name: OXE-01, manufactured by BASF), 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazole-3-yl]ethanone 1-(0-acetyloxime) (trade name: OXE-02, manufactured by BASF), etc.; α-aminoalkylphenone compound is selected from at least one of 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-butane-1-one, 2-methyl-1-[4-(methylthio)phenyl]-2-morpholinopropane-1-one, etc.
[0099] Furthermore, the solvent E can dissolve the components in the photosensitive resin composition without special limitation, and examples thereof include: N-methylpyrrolidone, N,N-dimethylacetamide, N,N-dimethylformamide, N-vinylpyrrolidone, N,N-diethylformamide, γ-butyrolactone, ethyl lactate; methyl monoglycol dimethyl ether, methyl diglycol dimethyl ether, methyl triglycol dimethyl ether, ethyl monoglycol dimethyl ether, ethyl diglycol dimethyl ether, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, propylene glycol monomethyl ether, propylene glycol monoethyl ether, ethylene glycol dimethyl ether, ethylene glycol diethyl ether, etc., and one, two or more solvents can be used.
[0100] In addition, the photosensitive resin composition may further contain additives such as a thermal crosslinking agent, a curing accelerator, a stabilizer, a leveling agent, a defoaming agent, etc., as required. These additives may be selected according to reports in the prior art.
[0101] Further, the mass ratio of the alkali-soluble resin B (in terms of solid content) to the polyamic acid microspheres A is 100:30-800, for example, 100:30, 100:35, 100:40, 100:45, 100:50, 100:55, 100:60, 100:65, 100:70, 100:75, 100:80, 100:85, 100:90, 100:95, 100:100, 100:110, 100:120, 100:130, 100:140, 100:150, 100:160, 100:170, 100:180, 100:190, 100:201, 100:210, 100:220, 100:230, 100:240, 100:250, 100:261, 100:270, 100:280, 100:290, 100:300, 100:315 00:140、100:150、100:160、100:170、100:180、100:190、100:200、100:210、100:220、100:230、100:240、100:250、100:260、100:270、100:280、100:290、100:300、100:310、100:320、100:330、100:340、100:350、100 :360、100:370、100:380、100:390、100:400、100:410、100:420、100:430、100:440、100:450、100:460、100:470、100:480、100:490、100:500、100:510、100:520、100:530、100:540、100:550、100:560、100:570、100:5 : 80, 100:590, 100:600, 100:610, 100:620, 100:630, 100:640, 100:650, 100:660, 100:670, 100:680, 100:690, 100:700, 100:710, 100:720, 100:730, 100:740, 100:750, 100:760, 100:770, 100:780, 100:790, 100:800.
[0102] Further, the mass ratio of the alkali-soluble resin B (based on solid content) to the crosslinking agent C is 100:30-300, for example, 100:30, 100:35, 100:40, 100:45, 100:50, 100:55, 100:60, 100:65, 100:70, 100:75, 100:80, 100:85, 100:90, 100:95, 100:100, 100:1 100:120, 100:130, 100:140, 100:150, 100:160, 100:170, 100:180, 100:190, 100:200, 100:210, 100:220, 100:230, 100:240, 100:250, 100:260, 100:270, 100:280, 100:290, 100:300.
[0103] Further, the mass ratio of the alkali-soluble resin B (based on solid content) to the photoinitiator D is 100:0.1-30, for example, 100:0.1, 100:0.5, 100:1, 100:2, 100:3, 100:4, 100:5, 100:6, 100:7, 100:8, 100:9, 100:10, 100:11, 100:12, 100:13, 100:14, 100:15, 100:16, 100:17, 100:18, 100:19, 100:20, 100:21, 100:22, 100:23, 100:24, 100:25, 100:26, 100:27, 100:28, 100:29, 100:30, 100:31, 100:32, 100:33, 100:34, 100:35, 100:36, 100:37, 100:38, 100:39, 100:40, 100:41, 100:42, 100:43, 100:44, 100:45, 100:46, 100:47, 100:48, 100:49, 100:50, 100:51, 100:52, 100:5 0:12, 100:13, 100:14, 100:15, 100:16, 100:17, 100:18, 100:19, 100:20, 100:21, 100:22, 100:23, 100:24, 100:25, 100:26, 100:27, 100:28, 100:29, 100:30.
[0104] Further, the mass ratio of the alkali-soluble resin B (in terms of solid content) to the solvent E is 100:70-1500, for example, 100:70, 100:75, 100:80, 100:85, 100:90, 100:95, 100:100, 100:110, 100:120, 100:130, 100:140, 100:150, 100:160, 100:170, 100:180, 100:190, 100:200, 100:210, 100:220, 100:230, 100:240, 100:250 :250, 100:260, 100:270, 100:280, 100:290, 100:300, 100:400, 100:450, 100:500, 100:550, 100:600, 100:650, 100:700, 100:750, 100:800, 100:850, 100:900, 100:950, 100:1000, 100:1100, 100:1200, 100:1300, 100:1400, 100:1500, preferably 100:100-800.
[0105] The present invention also provides a method for preparing the above-mentioned photosensitive resin composition. The preparation of the photosensitive resin composition of the present invention is preferably completed in a Class 1000 clean room equipped with a yellow light source, especially at room temperature, by adding the formulated amount of polyimide microspheres A, alkali-soluble resin B, crosslinking agent C, and photoinitiator D to solvent E and stirring evenly to obtain the composition.
[0106] In order to ensure the purity of the photosensitive resin composition, the photosensitive resin composition may be filtered using a filtering device such as filter paper, filter membrane, filter, etc. The filtering method is not particularly limited, but pressure filtration using a filter with a pore size of 1 to 10 μm is preferred.
[0107] The present invention also provides a photosensitive resin sheet, which includes a supporting substrate, and the supporting substrate is covered with a cured film formed by a photosensitive resin composition varnish. There is no particular limitation on the supporting substrate, and various films on the market such as polyethylene terephthalate (PET) film, polyphenylene sulfide film, polyimide, etc. can be used. In order to improve the adhesiveness and peelability, the bonding surface between the supporting substrate and the photosensitive resin composition film can be surface treated with silicone, silane coupling agent, aluminum chelating agent, polyurea, etc. There is no particular limitation on the thickness of the supporting substrate, and from the perspective of operability, it is preferably 10 to 100 μm.
[0108] The photosensitive resin sheet of the present invention can be obtained by coating a photosensitive resin composition varnish on a supporting substrate and then drying to obtain a solidified film. The photosensitive resin composition varnish can be obtained by adding an organic solvent to the photosensitive resin composition of the present invention. The organic solvent is selected according to the coating effect of the photosensitive resin composition varnish on the supporting substrate. It can be a solvent used in the preparation process of the photosensitive resin composition or another organic solvent, and there is no special limitation. The following can be listed: ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, propylene glycol monomethyl ether, propylene glycol monoethyl ether, ethylene glycol dimethyl ether, ethylene glycol diethyl ether, ethylene glycol dibutyl ether, ethylene glycol monoethyl ether acetate, propylene glycol monomethyl ether acetate, propyl acetate, butyl acetate, isobutyl acetate, 3-methoxybutyl acetate, 3-methyl-3-methoxybutyl acetate, methyl lactate, ethyl lactate, butyl lactate, butyl lactate; acetone, methyl ethyl acetone, methyl propyl ketone, methyl butyl ketone, methyl isobutyl ketone, cyclopentanone, 2-heptanone, butanol, isobutanol, pentanol, 4-methyl-2-pentanol, 3-methyl-2-butanol, 3-methyl-3-methoxybutanol, diacetone alcohol, toluene, xylene, N-methylpyrrolidone, N-cyclohexylpyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, γ-butyrolactone, etc.
[0109] In order to ensure the purity of the photosensitive resin composition varnish, the photosensitive resin composition varnish may be filtered using a filtering device such as filter paper, filter membrane, filter, etc. The filtering method is not particularly limited, but pressure filtration using a filter with a pore size of 1 to 10 μm is preferred.
[0110] As a method for coating the photosensitive resin composition varnish on the substrate, spin coating, spray coating, roll coating, screen printing, or coating methods using a blade coater, a calender coater, a slit coater, a roll coater, a comma roll coater, a gravure coater, etc. can be cited. The coating film thickness varies depending on the coating method, the solid content of the varnish, the viscosity of the varnish, etc., and the film thickness after drying is preferably in the range of 0.5 to 100 μm.
[0111] The drying method can be an oven, a heating plate, an infrared heater, etc. The drying temperature and the drying time can be controlled within the range that allows the organic solvent to volatilize. It is preferred to appropriately set the photosensitive resin composition film to an uncured or semi-cured state. The specific drying temperature is preferably 40 to 120°C, and the drying time is preferably 1 to 60 minutes. Furthermore, staged heating can also be used, for example, heat treatment at 70°C, 80°C, and 90°C for 1 minute each.
[0112] In addition, the photosensitive resin sheet can be protected by a protective film to avoid the influence of pollutants such as dust and dirt in the air. Examples of the protective film include polyethylene film, polypropylene film, polyester film, etc. The protective film is preferably a film with low adhesion to the photosensitive resin composition film.
[0113] The photosensitive resin composition and the photosensitive resin sheet of the present invention are suitable for surface protection films of semiconductor elements, ultra-thin flexible circuit boards, interlayer insulation films, and insulation layers of organic electroluminescent elements. In the present invention, an electronic component or semiconductor device is specifically provided, wherein the electronic component or semiconductor device is bonded to multiple substrates or to other components through the cured film of the photosensitive resin composition of the present invention. The cured film of the photosensitive resin composition can be prepared by directly coating the photosensitive resin composition on a substrate, or can be introduced in the form of a photosensitive resin sheet.
[0114] When preparing a semiconductor device, the steps may be: affixing a photosensitive resin sheet or coating a photosensitive resin composition on a semiconductor wafer having an image sensor element to form a photosensitive resin composition film. Exposing and developing the photosensitive resin composition film, removing the resin film on the sensor portion, and retaining the resin film around the sensor. A substrate is attached to the retained photosensitive resin composition film and thermally pressed. The photosensitive resin composition film is heated to cure, and the semiconductor wafer and the substrate are bonded via the photosensitive resin composition film to obtain an image sensor wafer with a hollow structure of a wiring pattern.
[0115] Furthermore, the method of forming a photosensitive resin composition film on a substrate by the photosensitive resin composition may include spin coating, spray coating, roller coating, screen printing and the like. In addition, the coating film thickness varies depending on the coating method, the solid content and viscosity of the photosensitive resin composition, but the thickness of the film after drying is preferably 0.5 to 100 μm. The substrate coated with the photosensitive resin composition is dried to obtain a photosensitive resin composition film, which can be dried using an oven, a heating plate, an infrared heater, and the like. The drying temperature and drying time are within the range that allows the organic solvent to volatilize, and are preferably set to a range in which the photosensitive resin composition film becomes an uncured or semi-cured state. For example, it is preferably dried at a temperature range of 50 to 150° C. for 1 to 60 minutes.
[0116] As substrates for electronic components or semiconductor devices, semiconductor substrates, organic substrates, inorganic substrates, and semiconductor elements or circuit substrates of circuits arranged on these substrates can be cited, but are not limited to these. As examples of semiconductor substrates, semiconductor wafers such as silicon or gallium arsenic or substrates cut therefrom can be cited. As examples of organic substrates, glass cloth epoxy copper foil laminates can be cited; heat-resistant thermoplastic substrates such as polyetherimide resin substrates, polyether ketone resin substrates, and polysulfone resin substrates; flexible substrates such as polyester copper foil film substrates and polyimide copper foil film substrates can be cited. As examples of inorganic substrates, ceramic substrates such as alumina substrates, aluminum nitride substrates, and silicon carbide substrates can be cited; metal substrates such as aluminum raw material substrates and iron raw material substrates; and glass substrates can be cited. As circuit substrates, conductors containing metals such as silver, gold, and copper, resistors containing inorganic oxides, low dielectrics containing glass materials and / or resins, high dielectrics containing resins or high dielectric constant inorganic particles, and insulators containing glass materials can be cited.
[0117] On the other hand, when using a photosensitive resin sheet, the protective film must be peeled off first, so that the photosensitive resin sheet and the substrate are opposite to each other and bonded by thermocompression bonding. Thermocompression bonding can be performed by thermal sub-treatment, thermal lamination treatment, thermal vacuum lamination treatment, etc. Considering the adhesion to the substrate, the thermocompression bonding temperature is preferably above 40°C. In addition, in order to prevent the resolution of the photosensitive resin sheet from being deteriorated during curing, exposure, and pattern formation in the development process during thermocompression bonding, the thermocompression bonding temperature is preferably below 150°C. After thermocompression bonding, the support film is peeled off, and the photosensitive resin composition film is retained on the substrate.
[0118] The obtained photosensitive resin composition film is irradiated with chemical rays through a mask plate for exposure. As chemical rays used for exposure, there are ultraviolet rays, visible rays, electron rays, X-rays, etc. In the present invention, it is preferred to use i-rays (365nm), h-rays (405nm) or g-rays (436nm) of a mercury lamp. For the photosensitive resin sheet, when the support film is a transparent material, it is also possible to expose without peeling the support film from the photosensitive resin sheet.
[0119] When forming a pattern, the unexposed part is removed with a developer after exposure. As a developer, tetramethylammonium, diethanolamine, diethylaminoethanol, sodium hydroxide, potassium hydroxide, sodium carbonate, potassium carbonate, triethylamine, diethylamine, methylamine, dimethylamine, dimethylaminoethyl acetate, dimethylaminoethanol, dimethylaminoethyl methacrylate, cyclohexylamine, ethylenediamine, 1,6-hexanediamine and other alkaline compound aqueous solutions are preferred. Depending on the circumstances, one or more polar solvents selected from N-methylpyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, γ-butyrolactone, dimethylacrylamide and the like; alcohols such as methanol, ethanol, isopropanol; esters such as ethyl lactate and propylene glycol azomethyl ether acetate; compounds such as cyclopentanone, cyclohexanone, isobutyl ketone, and methyl isobutyl ketone may also be added to these alkaline aqueous solutions.
[0120] The development can be carried out by spraying the above-mentioned developer on the film-attached surface of the substrate or immersing the film in the developer together with the substrate, or by applying ultrasonic waves while immersing the substrate in the developer. In addition, the developer can be sprayed on the film surface while rotating the substrate. The development time, development steps, and temperature of the developer are not limited, as long as the unexposed portion can be removed. In order to process fine patterns or remove residues between patterns, it is preferred to further develop after removing the unexposed portion.
[0121] After development, the film may be rinsed with water. Alcohol such as ethanol or isopropyl alcohol and ethyl lactate, propylene glycol monomethyl ether acetate, etc. may be added to water for rinsing.
[0122] In order to further improve the resolution and expand the development process range, a baking treatment may be performed before development. The baking treatment temperature is preferably 50 to 180° C., more preferably 60 to 120° C. The baking treatment time is preferably 5 s to 60 min.
[0123] From the viewpoint of reducing the solvent, solid content, water content, etc. of the photosensitive resin composition film remaining after pattern formation, it is preferably heated and dried at 60 to 200° C. The heating and drying time is preferably 1 to 60 minutes.
[0124] The substrate with the patterned photosensitive resin composition film is thermally pressed onto another substrate or other hanging parts. The thermal pressing temperature can be above the glass transition temperature of the resin composition film, preferably 100 to 400°C, and the pressure during pressing is preferably 0.01 to 10 MPa, and the time is preferably 1 second to 10 minutes.
[0125] After the thermal compression bonding, the photosensitive resin composition film is cured by applying 120 to 400° C., preferably 180 to 250° C. The curing temperature can be increased stepwise or continuously within a specified temperature range. The heating treatment time is preferably 5 min to 5 h.
[0126] The thickness of the cured film can be arbitrarily set, but is preferably 0.5 μm to 100 μm.
[0127] The present invention has the following beneficial effects:
[0128] The photosensitive resin composition of the present invention contains polyamic acid microspheres with high crosslinking density. The polyamic acid microspheres have good dispersibility in the photosensitive resin composition, can be developed by an alkaline developer after exposure, and have high resolution. At the same time, the benzimidazole structure contained in the composition can improve the adhesion performance of the polyimide film to the substrate, and can effectively prevent the surface oxidation and discoloration of the copper substrate. Therefore, the prepared cured film has high modulus, excellent mechanical properties, good adhesion to the substrate, and can effectively prevent the surface oxidation and discoloration of the copper substrate. The film can be used in the fields of semiconductor elements requiring high modulus, high resolution, and high mechanical strength, and has broad application prospects. DETAILED DESCRIPTION
[0129] The present invention is further described below in conjunction with specific examples, but the present invention is not limited to the following examples. The methods are conventional methods unless otherwise specified. The materials can be purchased from public commercial channels unless otherwise specified.
[0130] Preparation Example 1
[0131] Synthesis of diamine monomer b-1
[0132]
[0133] (1) Compound 2 (0.15 mol, 25.83 g) was dissolved in 0°C dry dichloromethane (500 ml), BF3·OEt2 (0.1 mol, 14.19 g) was added dropwise, and then compound 1 (0.1 mol, 14.26 g) was added. The reaction was stirred at room temperature for 2 h and detected by TLC plate. When compound 1 was completely reacted, saturated NaHCO3 aqueous solution was added to the reaction system to quench the reaction. The reaction was extracted three times with 1500 ml of dichloromethane, the organic phases were combined, dried with anhydrous MgSO4, filtered, and the solvent was distilled off under reduced pressure. Compound 3 was obtained as a colorless oil by column chromatography, with a mass of 16.74 g and a yield of 81%.
[0134]
[0135] (2) In a nitrogen atmosphere, dimethylformamide (55 g), potassium carbonate (0.16 mol, 22.11 g), compound 3 (0.08 mol, 16.53 g) and compound 4 (0.08 mol, 14.73 g) were added to a three-necked flask, heated to 80°C and stirred for 16 hours. Thereafter, the inorganic salts were removed by vacuum filtration, and the filtrate was diluted with ethyl acetate (110 g). The organic phase was washed three times with pure water (110 g), dried with anhydrous magnesium sulfate, and then the solvent was removed by vacuum distillation to obtain a yellow solid compound 5 with a mass of 24.38 g and a yield of 86%.
[0136]
[0137] (3) At room temperature, zinc powder (0.9 mol, 58.84 g) and glacial acetic acid (0.9 mol, 54.05 g) were added to an anhydrous ethanol (500 ml) solution containing compound 5 (60 mmol), stirred for 1 h, and filtered with diatomaceous earth. Anhydrous ethanol was removed by vacuum distillation, saturated NaHCO3 solution (500 ml) was added, and the mixture was extracted three times with 500 ml of ethyl acetate. The organic phase was washed three times with saturated NaCl solution, dried over anhydrous MgSO4, filtered, and the organic solvent was removed by vacuum distillation to obtain a white solid b-1 with a mass of 16.78 g and a yield of 95%.
[0138] B-1 NMR information is as follows:
[0139] 1 HNMR(DMSO): δ: 2.29(m,2H),2.59(m,2H),4.88(d,1H),5.13(d,1H),5.28(s,4H) ,5.76(s,3H),5.82(m,1H),6.97(d,1H),7.18(s,1H),7.52(d,1H),12.19(s,1H).
[0140] Preparation Example 2
[0141] Synthesis of diamine monomer b-2
[0142] (1) Compound 3 was synthesized according to the method of Synthesis Example 1.
[0143]
[0144] (2) In a nitrogen atmosphere, dimethylformamide (55 g), potassium carbonate (0.16 mol, 22.11 g), compound 3 (0.08 mol, 16.53 g) and compound 6 (0.08 mol, 14.73 g) were added to a three-necked flask and heated at 80°C with stirring for 16 hours. Thereafter, the inorganic salts were removed by vacuum filtration, and the filtrate was diluted with ethyl acetate (110 g). The organic phase was washed three times with pure water (110 g), dried with anhydrous magnesium sulfate, and then the solvent was removed by vacuum distillation to obtain a yellow solid compound 7 with a mass of 24.66 g and a yield of 87%.
[0145]
[0146] (3) At room temperature, zinc powder (0.9 mol, 58.84 g) and glacial acetic acid (0.9 mol, 54.05 g) were added to an anhydrous ethanol (500 ml) solution containing compound 7 (60 mmol), stirred for 1 h, and filtered with diatomaceous earth. Anhydrous ethanol was removed by vacuum distillation, saturated NaHCO3 solution (500 ml) was added, and the mixture was extracted three times with 500 ml of ethyl acetate. The organic phase was washed three times with saturated NaCl solution, dried over anhydrous MgSO4, filtered, and the organic solvent was removed by vacuum distillation to obtain a white solid b-2 with a mass of 16.60 g and a yield of 94%.
[0147] B-2 NMR information is as follows:
[0148] 1 HNMR(DMSO): δ: 2.29(m,2H),2.59(m,2H),4.88(d,1H),5.13(d,1H),5.28(s,4H),5.82(m,1H) ,6.03(s,1H),6.19(d,1H),6.70(d,1H),6.97(d,1H),7.18(s,1H),7.52(d,1H),12.19(s,1H).
[0149] Preparation Example 3
[0150] Synthesis of diamine monomer b-3
[0151] (1) Compound 3 was synthesized according to the method of Synthesis Example 1.
[0152]
[0153] (2) In a nitrogen atmosphere, dimethylformamide (55 g), potassium carbonate (0.16 mol, 22.11 g), compound 3 (0.08 mol, 16.53 g) and compound 8 (0.08 mol, 14.73 g) were added to a three-necked flask and heated at 80°C with stirring for 16 hours. Thereafter, the inorganic salts were removed by filtration under reduced pressure, and the filtrate was diluted with ethyl acetate (110 g). The organic phase was washed three times with pure water (110 g), dried with anhydrous magnesium sulfate, and then the solvent was removed by distillation under reduced pressure to obtain yellow solid compound 9, with a mass of 24.09 g and a yield of 85%.
[0154]
[0155] (3) At room temperature, zinc powder (0.9 mol, 58.84 g) and glacial acetic acid (0.9 mol, 54.05 g) were added to an anhydrous ethanol (500 ml) solution containing compound 9 (60 mmol), stirred for 1 h, and filtered with diatomaceous earth. The anhydrous ethanol was removed by vacuum distillation, saturated NaHCO3 solution (500 ml) was added, and the mixture was extracted three times with 500 ml of ethyl acetate. The organic phase was washed three times with saturated NaCl solution, dried over anhydrous MgSO4, filtered, and the organic solvent was removed by vacuum distillation to obtain a white solid b-3 with a mass of 16.43 g and a yield of 93%.
[0156] B-3 NMR information is as follows:
[0157] 1 HNMR(DMSO): δ: 2.29(m,2H),2.59(m,2H),4.88(d,1H),4.94(s,4H),5.13(d,1H),5.82(m,1H) ,6.20(s,1H),6.33(d,1H),6.60(d,1H),6.97(d,1H),7.18(s,1H),7.52(d,1H),12.19(s,1H).
[0158] Preparation Example 4
[0159] Synthesis of diamine monomer b-4
[0160] (1) Compound 3 was synthesized according to the method of Synthesis Example 1.
[0161]
[0162] (2) In a nitrogen atmosphere, dimethylformamide (55 g), potassium carbonate (0.16 mol, 22.11 g), compound 3 (0.08 mol, 16.53 g) and compound 10 (0.08 mol, 14.73 g) were added to a three-necked flask and heated at 80°C with stirring for 16 hours. Thereafter, the inorganic salts were removed by filtration under reduced pressure, and the filtrate was diluted with ethyl acetate (110 g). The organic phase was washed three times with pure water (110 g), dried with anhydrous magnesium sulfate, and then the solvent was removed by distillation under reduced pressure to obtain a yellow solid compound 11 with a mass of 23.81 g and a yield of 84%.
[0163]
[0164] (3) At room temperature, zinc powder (0.9 mol, 58.84 g) and glacial acetic acid (0.9 mol, 54.05 g) were added to an anhydrous ethanol (500 ml) solution containing compound 11 (60 mmol), stirred for 1 h, and filtered with diatomaceous earth. Anhydrous ethanol was removed by vacuum distillation, saturated NaHCO3 solution (500 ml) was added, and the mixture was extracted three times with 500 ml of ethyl acetate. The organic phase was washed three times with saturated NaCl solution, dried over anhydrous MgSO4, filtered, and the organic solvent was removed by vacuum distillation to obtain a white solid b-4 with a mass of 16.78 g and a yield of 95%.
[0165] B-4 NMR information is as follows:
[0166] 1 HNMR(DMSO): δ: 2.29(m,2H),2.59(m,2H),4.82(s,2H),4.88(d,1H),4.94(s,2H),5.13(d,1H),5.82( m,1H),6.30(d,1H),6.47(d,1H),6.53(d,1H),6.97(d,1H),7.18(s,1H),7.52(d,1H),12.19(s,1H).
[0167] Preparation Example 5
[0168] Synthesis of diamine monomer b-5
[0169] (1) Compound 3 was synthesized according to the method of Synthesis Example 1.
[0170]
[0171] (2) In a nitrogen atmosphere, dimethylformamide (55 g), potassium carbonate (0.16 mol, 22.11 g), compound 3 (0.08 mol, 16.53 g) and compound 12 (0.08 mol, 15.85 g) were added to a three-necked flask and heated at 80°C with stirring for 16 hours. Thereafter, the inorganic salts were removed by vacuum filtration, and the filtrate was diluted with ethyl acetate (110 g). The organic phase was washed three times with pure water (110 g), dried with anhydrous magnesium sulfate, and then the solvent was removed by vacuum distillation to obtain a yellow solid compound 13 with a mass of 25.05 g and a yield of 85%.
[0172]
[0173] (3) At room temperature, zinc powder (0.9 mol, 58.84 g) and glacial acetic acid (0.9 mol, 54.05 g) were added to an anhydrous ethanol (500 ml) solution containing compound 13 (60 mmol), stirred for 1 h, and filtered with diatomaceous earth. Anhydrous ethanol was removed by vacuum distillation, saturated NaHCO3 solution (500 ml) was added, and the mixture was extracted three times with 500 ml of ethyl acetate. The organic phase was washed three times with saturated NaCl solution, dried over anhydrous MgSO4, filtered, and the organic solvent was removed by vacuum distillation to obtain a white solid b-5 with a mass of 17.58 g and a yield of 95%.
[0174] B-5 NMR information is as follows:
[0175] 1 HNMR(DMSO): δ: 2.15(s,3H),2.29(m,2H),2.59(m,2H),4.88(d,1H),4.94(s,4H),5.13(d,1H) ,5.82(m,1H),6.28(s,1H),6.68(s,1H),6.97(d,1H),7.18(s,1H),7.52(d,1H),12.19(s,1H).
[0176] Preparation Example 6
[0177] Synthesis of diamine monomer b-6
[0178] (1) Compound 3 was synthesized according to the method of Synthesis Example 1.
[0179]
[0180] (2) In a nitrogen atmosphere, dimethylformamide (55 g), potassium carbonate (0.16 mol, 22.11 g), compound 3 (0.08 mol, 16.53 g) and compound 14 (0.08 mol, 20.66 g) were added to a three-necked flask and heated at 80°C with stirring for 16 hours. Thereafter, the inorganic salts were removed by filtration under reduced pressure, and the filtrate was diluted with ethyl acetate (110 g). The organic phase was washed three times with pure water (110 g), dried with anhydrous magnesium sulfate, and then the solvent was removed by distillation under reduced pressure to obtain a yellow solid compound 15 with a mass of 28.10 g and a yield of 82%.
[0181]
[0182] (3) At room temperature, zinc powder (0.9 mol, 58.84 g) and glacial acetic acid (0.9 mol, 54.05 g) were added to an anhydrous ethanol (500 ml) solution containing compound 15 (60 mmol), stirred for 1 h, and filtered with diatomaceous earth. The anhydrous ethanol was removed by vacuum distillation, saturated NaHCO3 solution (500 ml) was added, and the mixture was extracted three times with 500 ml of ethyl acetate. The organic phase was washed three times with saturated NaCl solution, dried over anhydrous MgSO4, filtered, and the organic solvent was removed by vacuum distillation to obtain a white solid b-6 with a mass of 20.56 g and a yield of 93%.
[0183] B-6 NMR information is as follows:
[0184] 1 HNMR(DMSO): δ: 2.29(m,2H),2.59(m,2H),3.40(m,3H),3.77(m,2H),4.31(m,2H),4.88(d,1H),4.94(s,4H) ,5.13(d,1H),5.82(m,1H),6.25(s,1H),6.33(s,1H),6.97(d,1H),7.18(s,1H),7.52(d,1H),12.19(s,1H).
[0185] Preparation Example 7
[0186] Synthesis of diamine monomer b-7
[0187] (1) Compound 3 was synthesized according to the method of Synthesis Example 1.
[0188]
[0189] (2) In a nitrogen atmosphere, dimethylformamide (55 g), potassium carbonate (0.16 mol, 22.11 g), compound 3 (0.08 mol, 16.53 g) and compound 16 (0.08 mol, 18.73 g) were added to a three-necked flask and heated at 80°C with stirring for 16 hours. Thereafter, the inorganic salts were removed by filtration under reduced pressure, and the filtrate was diluted with ethyl acetate (110 g). The organic phase was washed three times with pure water (110 g), dried with anhydrous magnesium sulfate, and then the solvent was removed by distillation under reduced pressure to obtain yellow solid compound 17, with a mass of 26.85 g and a yield of 83%.
[0190]
[0191] (3) At room temperature, zinc powder (0.9 mol, 58.84 g) and glacial acetic acid (0.9 mol, 54.05 g) were added to an anhydrous ethanol (500 ml) solution containing compound 17 (60 mmol), stirred for 1 h, and filtered with diatomaceous earth. Anhydrous ethanol was removed by vacuum distillation, saturated NaHCO3 solution (500 ml) was added, and the mixture was extracted three times with 500 ml of ethyl acetate. The organic phase was washed three times with saturated NaCl solution, dried over anhydrous MgSO4, filtered, and the organic solvent was removed by vacuum distillation to obtain a white solid b-7 with a mass of 19.43 g and a yield of 94%.
[0192] B-7 NMR information is as follows:
[0193] 1 HNMR(DMSO): δ: 2.29(m,2H),2.59(m,2H),4.62(s,2H),4.88(d,1H),5.13(d,1H),5.59(s,2H),5.82(m,1H) ,6.08(d,1H),6.67(d,1H),6.77(s,1H),6.98(d,2H),7.18(s,1H),7.52(d,1H),7.80(d,1H),12.19(s,1H).
[0194] Preparation Example 8
[0195] Synthesis of diamine monomer b-8
[0196] (1) Compound 3 was synthesized according to the method of Synthesis Example 1.
[0197]
[0198] (2) In a nitrogen atmosphere, dimethylformamide (55 g), potassium carbonate (0.16 mol, 22.11 g), compound 3 (0.08 mol, 16.53 g) and compound 18 (0.08 mol, 16.01 g) were added to a three-necked flask and heated at 80°C with stirring for 16 hours. Thereafter, the inorganic salts were removed by filtration under reduced pressure, and the filtrate was diluted with ethyl acetate (110 g). The organic phase was washed three times with pure water (110 g), dried over anhydrous magnesium sulfate, and then the solvent was removed by distillation under reduced pressure to obtain yellow solid compound 19, with a mass of 25.18 g and a yield of 85%.
[0199]
[0200] (3) At room temperature, zinc powder (0.9 mol, 58.84 g) and glacial acetic acid (0.9 mol, 54.05 g) were added to an anhydrous ethanol (500 ml) solution containing compound 19 (60 mmol), stirred for 1 h, and filtered through diatomaceous earth. Anhydrous ethanol was removed by vacuum distillation, saturated NaHCO3 solution (500 ml) was added, and the mixture was extracted three times with 500 ml of ethyl acetate. The organic phase was washed three times with saturated NaCl solution, dried over anhydrous MgSO4, filtered, and the organic solvent was removed by vacuum distillation to obtain 16.76 g of white solid b-8 with a yield of 90%.
[0201] B-8 NMR information is as follows:
[0202] 1 HNMR(DMSO): δ: 2.29(m,2H),2.59(m,2H),4.77(s,4H),4.88(d,1H),5.13(d,1H),5.82( m,1H),6.18(m,2H),6.97(d,1H),7.18(s,1H),7.52(d,1H),9.58(d,1H),12.19(s,1H).
[0203] Preparation Example 9
[0204] Synthesis of diamine monomer b-9
[0205] (1) Compound 3 was synthesized according to the method of Synthesis Example 1.
[0206]
[0207] (2) In a nitrogen atmosphere, dimethylformamide (47 g), potassium carbonate (0.16 mol, 22.11 g), compound 3 (0.08 mol, 16.53 g) and compound 18 (0.04 mol, 8.00 g) were added to a three-necked flask and heated at 80° C. with stirring for 16 hours. Thereafter, inorganic salts were removed by filtration under reduced pressure, and the filtrate was diluted with ethyl acetate (110 g). The organic phase was washed three times with pure water (110 g), dried with anhydrous magnesium sulfate, and then the solvent was removed by distillation under reduced pressure to obtain yellow solid compound 20, with a mass of 18.16 g and a yield of 84%.
[0208]
[0209] (3) At room temperature, zinc powder (0.45 mol, 29.42 g) and glacial acetic acid (0.45 mol, 27.02 g) were added to an anhydrous ethanol (300 ml) solution containing compound 20 (30 mmol), stirred for 1 h, and filtered with diatomaceous earth. Anhydrous ethanol was removed by vacuum distillation, saturated NaHCO3 solution (500 ml) was added, and the mixture was extracted three times with 300 ml of ethyl acetate. The organic phase was washed three times with saturated NaCl solution, dried over anhydrous MgSO4, filtered, and the organic solvent was removed by vacuum distillation to obtain a white solid b-9 with a mass of 13.26 g and a yield of 92%.
[0210] B-9 NMR information is as follows:
[0211] 1 HNMR(DMSO): δ: 2.29(m,4H),2.59(m,4H),4.77(s,4H),4.88(d,2H),5.13(d,2H) ,5.82(m,2H),6.33(d,2H),6.97(d,2H),7.18(s,2H),7.52(d,2H),12.19(s,2H).
[0212] Preparation Example 10
[0213] Synthesis of diamine monomer b-10
[0214] (1) Compound 3 was synthesized according to the method of Synthesis Example 1.
[0215]
[0216] (2) In a nitrogen atmosphere, dimethylformamide (47 g), potassium carbonate (0.16 mol, 22.11 g), compound 3 (0.08 mol, 16.53 g) and compound 21 (0.04 mol, 8.00 g) were added to a three-necked flask and heated at 80°C with stirring for 16 hours. Thereafter, the inorganic salts were removed by filtration under reduced pressure, and the filtrate was diluted with ethyl acetate (110 g). The organic phase was washed three times with pure water (110 g), dried with anhydrous magnesium sulfate, and then the solvent was removed by distillation under reduced pressure to obtain a yellow solid compound 22 with a mass of 18.38 g and a yield of 85%.
[0217]
[0218] (3) At room temperature, zinc powder (0.45 mol, 29.42 g) and glacial acetic acid (0.45 mol, 27.02 g) were added to an anhydrous ethanol (300 ml) solution containing compound 22 (30 mmol), stirred for 1 h, and filtered with diatomaceous earth. Anhydrous ethanol was removed by vacuum distillation, saturated NaHCO3 solution (500 ml) was added, and the mixture was extracted three times with 300 ml of ethyl acetate. The organic phase was washed three times with saturated NaCl solution, dried over anhydrous MgSO4, filtered, and the organic solvent was removed by vacuum distillation to obtain 13.41 g of white solid b-10 with a yield of 93%.
[0219] B-10 NMR information is as follows:
[0220] 1 HNMR(DMSO): δ: 2.29(m,4H),2.59(m,4H),4.82(s,2H),4.88(d,2H),4.94(s,2H),5.13( d,2H),5.82(m,2H),6.30(d,2H),6.97(d,2H),7.18(s,2H),7.52(d,2H),12.19(s,2H).
[0221] Synthesis example 1
[0222] Preparation of polyamic acid microspheres A-1
[0223] Under a nitrogen atmosphere, 3.10 g (0.01 mol) of 4,4'-oxydiphthalic anhydride (ODPA) and 35 g of N,N-dimethylacetamide (DMAC) were added to a three-necked flask, stirred to dissolve, and then 0.52 g (0.002 mol) of 2,2'-bis(3-amino-4-hydroxyphenyl)propane (BHAPP) and 2.35 g (0.008 mol) of b-1 were added, and the reaction was continued for 24 hours to obtain a polyamic acid solution. DMAC 79.65 g, triethylamine 1.62 g (0.016 mol), OXE-01 0.45 g (0.001 mol) were added, and stirring was continued for 1 h. 136.20 g of methanol was added dropwise, and stirred at room temperature for 2 h to obtain a polyamic acid emulsion. The polyamic acid emulsion was irradiated with 365 nm UV for photocrosslinking for 1 h. The emulsion was then poured into 500 ml of ultrapure water for precipitation. The polyamic acid microspheres A-1 were obtained after filtration and drying at 80 ° C. with an average particle size of 201 nm.
[0224] Synthesis example 2-16
[0225] Polyamic acid microspheres A-2 to A-16 were prepared according to the method of Synthesis Example 1, except that the aromatic dianhydride Y and diamine X used were shown in Table 1 below.
[0226] Table 1
[0227]
[0228] Note: In Table 1, the molar amount of aromatic dianhydride Y or diamine X is shown in brackets.
[0229] Wherein: the structural formula of b-11 is shown in Formula 6 below:
[0230]
[0231] Synthesis Example 17
[0232] Under a nitrogen atmosphere, 311.32 g (0.85 mol) of 2,2'-bis(3-amino-4-hydroxyphenyl)hexafluoropropane (BAHF), 12.43 g (0.05 mol) of 1,3-bis(3-aminopropyl)tetramethyldisiloxane (SiDA) and 21.83 g (0.20 mol) of 3-aminophenol (MAP) were dissolved in 984 g of γ-butyrolactone (GBL), and ODPA (310.21 g, 1.0 mol) was added. The mixture was stirred at 60°C for 1 hour, then heated to 180°C, stirred for 2 hours, and cooled to room temperature to obtain an alkali-soluble polyimide solution B with a solid content of 40%.
[0233] The molecular weight and imidization rate of the obtained polyimide were detected as follows:
[0234] Molecular weight: Alkali-soluble polyimide solution B was diluted in NMP (N-methylpyrrolidone) to obtain a solution with a solid content of 0.1 wt%. The solution was measured by gel permeation chromatography (GPC) using LC-20AD (Shimadzu Corporation, Japan) with N-methylpyrrolidone as the mobile phase. The molecular weights obtained were all weight average molecular weights (M w ).
[0235] Imidization rate: Alkaline soluble polyimide solution B was spin-coated on a 4-inch silicon wafer to form a film, baked at 100°C for 15 min, and the infrared absorption spectrum of the polyimide film was measured to confirm the absorption peak of the polyimide structure (1780cm -1 、1377cm -1 The silicon wafer coated with polyimide film was then heat treated at 300°C for 1.5 hours, and the infrared absorption spectrum was measured again. The intensity of 1377 cm before and after the heat treatment was compared. -1 The imidization rate of the polymer after heat treatment is set as 100%, and the imidization rate of the polymer before heat treatment is calculated according to the peak intensity ratio. After testing, the weight average molecular weight of the obtained alkali-soluble polyimide is 19573, and the imidization rate is 95%.
[0236] Example 1
[0237] 5 g of the polyamic acid microspheres A-1 prepared in Synthesis Example 1 was dissolved in 10 g of NMP (solvent E), and 3 g of the alkali-soluble polyimide solution B prepared in Synthesis Example 17, 1.5 g of ethoxylated bisphenol A dimethacrylate (cross-linker C), and 0.2 g of OXE-01 (photoinitiator D) were added. After fully dissolved, the mixture was filtered using a 2.0-micron filter membrane to obtain a photosensitive resin composition P-1.
[0238] Examples and Comparative Examples
[0239] Examples 2 to 20 and comparative examples 1 to 3 were prepared according to the method of Example 1 to obtain photosensitive resin compositions P-2 to P-23. The specific formulas are shown in Table 2.
[0240] Table 2
[0241]
[0242]
[0243] Note: In Table 2, the number in brackets indicates the weight of polyamic acid microspheres.
[0244] The resolution, modulus, tensile strength, adhesion and discoloration of the photosensitive resin composition prepared above were tested. The test results are shown in Table 3. The method is as follows:
[0245] 1. Resolution
[0246] The photosensitive resin composition in each embodiment and comparative example was coated on a PET support film with a thickness of 38 μm using a comma roller coater, dried at 100°C for 15 minutes, and a PE film with a thickness of 38 μm was attached as a protective film to obtain a photosensitive resin sheet. The protective film was peeled off, and the peeled surface was laminated on a silicon wafer using a lamination device (manufactured by Takatori, VTM-200M) under the conditions of a processing table temperature of 80°C, a roller temperature of 80°C, a pressure of 150 pa, a pasting speed of 5 mm / s, and a pasting pressure of 0.2 MPa. After tearing off the support film, a step profiler (KLA Tencor P-7) was used to test the film thickness. The film thickness of the photosensitive resin composition film was 40 μm. Ultraviolet light (i and g lines) was used with an exposure of 400 mJ / cm 2 , and expose through a mask. After exposure, spray development was performed using a 2.38wt% tetramethylammonium hydroxide water-based developer for 240s, and the unexposed portion was removed and rinsed with water. The pattern was observed using an optical microscope (MX63-F, Olympus) at a magnification of 20 times, and the minimum size of the through-hole pattern was taken as the resolution.
[0247] 2. Modulus
[0248] The photosensitive resin composition samples of each embodiment and comparative example were coated on a silicon wafer and soft-baked at 120°C for 3 minutes on a hot stage to obtain a photosensitive composition film. The film thickness was tested using a step profiler (KLA Tencor P-7). The film thickness of the photosensitive resin composition film was 40 μm. The film thickness was measured using an ultraviolet lamp (i and g line) with an exposure of 400 mJ / cm 2 , perform full exposure, after exposure, use 2.38wt% tetramethylammonium hydroxide water-based developer for spray development, the development time is 240s, rinse with water and then place the film in a vacuum oxygen-free oven (Zhenping Technology Co., Ltd., MOLZK-32D1), under nitrogen atmosphere protection, heat treat at 150°C for 30 minutes, then heat to 270°C after 1 hour, and treat at 270°C for 1 hour, then directly cool to below 50°C in the oven, and finally obtain a cured film. The cured film was cut into strips with a length of 15mm and a width of 3mm, and the modulus of the film was tested by DMA (TA, DMA850), the heating rate was 3°C / min, the frequency was 1.0Hz, and 5 strips were set, one highest value and one lowest value were removed, and the remaining 3 values were averaged to obtain the modulus.
[0249] 3. Tensile strength test
[0250] The cured film was obtained in the above-mentioned modulus method. The cured film was cut into strips with a length of 15 mm and a width of 3 mm, and the tensile strength of the film was tested by DMA (TA, DMA850). The tensile rate was 3 N / min, and 5 strips were collected in each group. The highest value and the lowest value were removed, and the remaining 3 values were averaged to obtain the tensile strength.
[0251] 4. Adhesion performance test
[0252] The photosensitive resin compositions of the embodiments and comparative examples were spin-coated on a 4-inch silicon wafer, and soft-baked at 120°C for 3 minutes on a hot stage to obtain a photosensitive composition film, which was then placed in a vacuum oxygen-free oven (Zhenping Technology Co., Ltd., MOLZK-32D1) for heat treatment. Specifically, the film was first heat-treated at 150°C for 30 minutes, then heated to 270°C for 1 hour to obtain a cured film, and the film thickness was tested using a step profiler (KLA Tencor P-7), and the film thickness was 40 μm.
[0253] The cured film was scored into 10 rows × 10 columns of grids using a grid marker (model: BYK-Gardner A-5125), and a peeling test was performed using tape (special transparent 3M tape) in accordance with the national standard GB / T 9286-1998 Cross-cutting test for paint and varnish films, and the number of grids peeled off was recorded as the peeling condition before PCT.
[0254] According to the same method as above, a grid machine (model, BYK-Gardner A-5125) was used to carve 10 rows × 10 columns of squares on the cured film. The cured film with the grids was first subjected to a 200-hour PCT test (121°C, 2 atmospheres of saturated steam; PCT-30 of Dongguan Hongjin Technology). After the PCT test was completed, a peeling test was performed using tape using the same method as above, and the number of unpeeled grids was recorded as the peeling condition after PCT.
[0255] When the number of peeled pieces in the adhesive peeling test was less than 10, the adhesiveness was considered to be good, and when it was 10 or more, the adhesiveness was considered to be poor.
[0256] The adhesion between the cured film sample prepared above and the substrate was tested according to the above-mentioned adhesion peeling test method.
[0257] 5. Copper discoloration test
[0258] The photosensitive resin compositions of the examples and comparative examples were spin-coated on a 4-inch copper sheet, and soft-baked at 120°C for 3 minutes on a hot plate to obtain a photosensitive composition film, which was spray-developed using a 2.38wt% tetramethylammonium hydroxide water-based developer, and rinsed with pure water to completely dissolve the coating film. The dissolved copper substrate was evaluated according to the following criteria:
[0259] “Excellent”: No discoloration of the copper substrate was observed even when observed under a 200x optical microscope;
[0260] "Good" means that there is a small amount of discoloration of the copper substrate when observed under a 200x optical microscope;
[0261] “Medium” shows a lot of discoloration of the copper substrate when observed with a 200x optical microscope;
[0262] "Poor" Severe discoloration of the copper substrate was observed by naked eyes.
[0263] Table 3
[0264]
[0265]
[0266] By comparing the data of Examples 1-10 and Comparative Examples 1-3 in Table 3, it can be seen that the film made from the photosensitive resin composition containing the polyamic acid microspheres of the present invention has excellent resolution, and the prepared cured film has high modulus, high tensile strength, good adhesion to the substrate, and can effectively prevent oxidation and discoloration of the copper substrate surface.
[0267] By comparing Examples 1-17 and Examples 18-20, it can be seen that Examples 13 and 14 have the best comprehensive effects. The combination of polyamic acid microspheres A-8 and A-9 or A-10 has better resolution, higher modulus and tensile strength, good adhesion to the substrate, and good resistance to oxidation and discoloration of the copper substrate surface.
[0268] By comparing Examples 1-14 and Examples 18-20, it can be seen that when ODPA, BHAPP are combined with the photopolymerizable diamine compound of the present invention, the obtained photosensitive resin composition of polyamic acid microspheres has excellent resolution, high modulus, high tensile strength, good viscosity with the substrate, and can effectively prevent oxidation and discoloration of the copper substrate surface.
[0269] In summary, the film made from the photosensitive resin composition containing polyamic acid microspheres of the present invention has excellent resolution, and the prepared cured film has high modulus, high tensile strength, good adhesion to the substrate, and can effectively prevent oxidation and discoloration of the copper substrate surface. It can be used in fields with high requirements for modulus and tensile strength, and has very high application value.
Claims
1. A photosensitive resin composition, characterized in that: The invention comprises polyamic acid microspheres A, alkali-soluble resin B, crosslinking agent C, photoinitiator D, and solvent E; the polyamic acid microspheres A are obtained by emulsifying and crosslinking polyamic acid, wherein the polyamic acid comprises polyamic acid obtained by polymerization reaction of diamine X and aromatic dianhydride Y; The diamine X includes a diamine compound X-1 and a diamine compound X-2, wherein the diamine compound X-1 is at least one of the photopolymerizable diamine compounds shown in Formula I; In formula I, Ar is phenyl or naphthyl; R1 is a hydrogen atom, a methyl group, an ethyl group, a hydroxyl group, or a methoxyethoxy group; R2 is a structure shown in the following formula II, wherein * is an insertion site, and m is 1 or 2; In formula II, R3 is methylene, ethylene, propylene or phenylene; R4 and R5 are each independently a hydrogen atom, a methyl group, an ethyl group, a propyl group or a phenyl group.
2. The photosensitive resin composition according to claim 1, characterized in that: The diamine compound X-1 is at least one of the compounds (b-1) to (b-10): (b-1) (b-2) (b-3) (b-4) (b-5) (b-6) (b-7) (b-8) (b-9) (b-10)。 3. The photosensitive resin composition according to claim 1 or 2, characterized in that: The diamine compound X-2 is selected from 2,2'-bis(3-amino-4-hydroxyphenyl)hexafluoropropane, 2,2'-bis(3-amino-4-hydroxyphenyl)propane, 3,3'-diamino-4,4'-dihydroxybiphenyl, 3,3'-dihydroxy-4,4'-diaminobiphenyl, 3,3'-diamino-4,4'-dihydroxydiphenylmethane, 3,3'-diamino-4,4'-dihydroxydiphenyl sulfide, 3,3'-diamino-4,4'-dihydroxydiphenyl sulfone, p-phenylenediamine, m-phenylenediamine, 2,5-diaminotoluene, 2,6-diaminotoluene, 4,4'-diaminodiphenyl ether, 3,4'-diaminodiphenyl at least one of ether, 3,3'-diaminodiphenyl ether, 2,4'-diaminodiphenyl ether, 4,4'-diaminodiphenylmethane, 3,3'-dimethyl-4,4'-diaminodiphenylmethane, 3,3',5,5'-tetramethyl-4,4'-diaminodiphenylmethane, 3,3',5,5'-tetraethyl-4,4'-diaminodiphenylmethane, 4,4'-bis(4-aminophenyl)propane, 4,4'-bis(4-aminophenoxy)diphenyl sulfone, 2,2'-trifluoromethyl-4,4'-diaminodiphenyl ether, 4,4'-bis(4-amino-2-trifluoromethylphenoxy)biphenyl, and 4,4'-diaminodiphenyl sulfone.
4. The photosensitive resin composition according to claim 1 or 2, characterized in that: The aromatic dianhydride Y is selected from at least one of pyromellitic dianhydride, 4,4'-oxydiphthalic anhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, 2,3',4,4'-biphenyltetracarboxylic dianhydride and 2,2',3,3'-benzophenonetetracarboxylic dianhydride.
5. The photosensitive resin composition according to claim 1 or 2, characterized in that: The content of the diamine compound X-1 is 50% to 100% of the total molar amount of the diamine X.
6. The photosensitive resin composition according to claim 1, wherein: When diamine X and aromatic dianhydride Y are used to prepare polyamic acid microspheres, the method comprises the following steps: diamine X and aromatic dianhydride Y are reacted in an organic solvent to obtain a polyamic acid solution, the polyamic acid solution is diluted with an organic solvent, an organic amine and a photoinitiator are added, stirred and mixed uniformly, and then a poor solvent is added and stirred and emulsified to obtain a polyamic acid emulsion, the polyamic acid emulsion is irradiated under ultraviolet light to perform crosslinking, and the product after crosslinking is precipitated in water, filtered, and dried to obtain polyamic acid microspheres.
7. The photosensitive resin composition according to claim 6, characterized in that: When preparing polyamic acid microspheres, at least one of the following conditions is included: a. The polyamic acid solution is diluted with an organic solvent to a polyamic acid mass concentration of 1 to 10%; b. The molar amount of the organic amine is 50 to 200% of the aromatic dianhydride Y; c. The mass of the photoinitiator is 0.1-20% of the mass of the polyamic acid; d. The mass of the poor solvent is 50-200% of the mass of the organic solvent in the diluted polyamic acid solution; e. The emulsification reaction temperature is 10~50℃, and the reaction time is 0.5~5h; f. The UV irradiation time is 0.5 to 8 hours; g. The organic amine includes triethylamine, the photoinitiator is the same as the photoinitiator D, and the poor solvent is selected from methanol, ethanol, water, and acetone.
8. The photosensitive resin composition according to claim 1, characterized in that: The alkali-soluble resin B is at least one of an alkali-soluble polyamic acid, an alkali-soluble polyamic acid ester, and an alkali-soluble polyimide, and the alkali-soluble resin B is obtained by reacting a tetracarboxylic dianhydride compound with a diamine compound.
9. The photosensitive resin composition according to claim 8, characterized in that: The tetracarboxylic dianhydride compound is selected from at least one of pyromellitic dianhydride, 3,4,3',4'-biphenyltetracarboxylic dianhydride, 4,4'-oxydiphthalic anhydride, 3,4,3',4'-benzophenonetetracarboxylic dianhydride, 3,3',4,4'-diphenylsulfonetetracarboxylic dianhydride, 2,3,6,7-naphthalenetetracarboxylic dianhydride, 4,4'-(hexafluoroisopropylidene)diphthalic anhydride and 1,2,3,4-cyclobutanetetracarboxylic dianhydride.
10. The photosensitive resin composition according to claim 8, characterized in that: The diamine compound is selected from 2,2'-bis(3-amino-4-hydroxyphenyl)hexafluoropropane, 2,2'-bis(3-amino-4-hydroxyphenyl)propane, 3,3'-diamino-4,4'-dihydroxybiphenyl, 3,3'-dihydroxy-4,4'-diaminobiphenyl, 3,3'-diamino-4,4'-dihydroxydiphenylmethane, 3,3'-diamino-4,4'-dihydroxydiphenyl sulfide, 3,3'-diamino-4,4'-dihydroxydiphenyl sulfone, p-phenylenediamine, m-phenylenediamine, 2,5-diaminotoluene, 2,6-diaminotoluene, 4,4'-diaminodiphenyl ether, 3,4'-diaminodiphenyl ether, 3,3'-diaminodiphenyl At least one of ether, 2,4'-diaminodiphenyl ether, 4,4'-diaminodiphenylmethane, 3,3'-dimethyl-4,4'-diaminodiphenylmethane, 3,3',5,5'-tetramethyl-4,4'-diaminodiphenylmethane, 3,3',5,5'-tetraethyl-4,4'-diaminodiphenylmethane, 4,4'-bis(4-aminophenyl)propane, 4,4'-bis(4-aminophenoxy)diphenyl sulfone, 2,2'-trifluoromethyl-4,4'-diaminodiphenyl ether, 4,4'-bis(4-amino-2-trifluoromethylphenoxy)biphenyl, 4,4'-diaminodiphenyl sulfone and 1,3-bis(3-aminopropyl)tetramethyldisiloxane.
11. The photosensitive resin composition according to claim 1, wherein: The crosslinking agent C is a photocrosslinking agent; the photoinitiator D is selected from at least one of benzophenone compounds, benzylidene compounds, coumarin compounds, anthraquinone compounds, benzoin compounds, thioxanthone compounds, thiol compounds, glycine compounds, oxime compounds, α-aminoalkylphenone compounds, 2,2'-bis(o-chlorophenyl)-4,4',5,5'-tetraphenylbiimidazole, and phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide.
12. The photosensitive resin composition according to claim 1, characterized in that: The weight average molecular weight of the alkali-soluble resin B is 10,000 or more and 100,000 or less.
13. The photosensitive resin composition according to claim 1, characterized in that: The mass ratio of the alkali-soluble resin B to the polyamic acid microspheres A is 100:30-800.
14. The photosensitive resin composition according to claim 1, characterized in that: The mass ratio of the alkali-soluble resin B to the cross-linking agent C is 100:30-300.
15. The photosensitive resin composition according to claim 1, characterized in that: The mass ratio of the alkali-soluble resin B to the photoinitiator D is 100:0.1-30.
16. The photosensitive resin composition according to claim 1, characterized in that: The mass ratio of the alkali-soluble resin B to the solvent E is 100:70-1500.
17. A photosensitive resin film, characterized in that: Obtained by curing the photosensitive resin composition according to any one of claims 1 to 16.
18. A photosensitive resin sheet, characterized in that: The invention comprises a supporting substrate, on which a cured film formed by a photosensitive resin composition varnish is coated; the photosensitive resin composition varnish is composed of the photosensitive resin composition according to any one of claims 1 to 16 and an organic solvent.
19. An electronic component or semiconductor device, characterized in that: The electronic component or semiconductor device is a device in which a plurality of substrates or a substrate and another member are bonded together via a cured product film of the photosensitive resin composition according to any one of claims 1 to 16.